Evaluation of Thermal Performance and Energy Efficiency of a Continuous Milk Pasteurization System Using a PTFE Pipe and Vegetable Oil Heating Medium - Agus Sutejo; Gilang Ramdani; Muhammad Juliandika; Dinur Saptiadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Continuous milk pasteurization systems require efficient heat transfer and energy utilization to ensure product safety and processing efficiency. However, the performance of systems utilizing alternative heating media, such as vegetable oil, is limitedly explored. This study aimed to evaluate a prototype continuous milk pasteurization system consisting of PTFE (Polytetrafluoroethylene) tubing submerged in vegetable oil heated by LPG. Experimental measurements (temperature at inlet/outlet, oil temperatures, mass flow) were combined with Computational Fluid Dynamics (CFD) using water as a surrogate fluid to analyze residence time, temperature rise, and heat-transfer performance under real operating conditions. At an oil average temperature of 131 °C, CFD and experiments showed milk reached a temperature of 72 °C after 6 m of tubing length, and then over the next 10 m. However, at an average flow speed of 0.955 m/s, the resulting residence time at ~72 °C was 10.47 s (below the HTST requirement of 15 s). Energy analysis indicated a fuel input of 1783.7 W, oil uptake of 634.4 W (35.6%), and useful heat of 139.5 W (7.8%), giving a system total efficiency of ~8.2%. Microbiological tests (Escherichia coli and Staphylococcus aureus) of treated samples complied with SNI ISO 7388:2009. Design modifications (longer tubing, alternative pipe materials, improved insulation, and heat recovery) are required to achieve HTST residence time and improve energy efficiency.